Stabilization policy in multi-country models - Nikolaus K. A. Läufer; Srinivasa Sundararajan (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
This paper analyzes the international transmission of economic distur-bances in a three-country world where two countries have no macroeconomic impact on a third country but are large enough to influence each other un-der fixed and flexible exchange rates. While the fixed exchange rate (FER) regime is shown to insulate the domestic economy from monetary shocks, the flexible exchange rate (FLER) regime is shown to be effective in dam-pening the impact of real shocks on domestic Output. As far as the shocks coming from the large country are concemed, the exchange rate flexibility serves as an important tool in reducing the variability of output.
Keywords: 330